Agile Governance through the SIKOJA Application: Driving Bureaucratic Reform in Jambi City Government - Syukri, Ahmad; Pratama, Rifqi Adha (Kemudi, 2025)
Public demands for government bureaucracy are increasingly strong in order to create agile, efficient, accountable, and high-quality public services. This study aims to determine how the Jambi City Government applies Agile Governance principles through the SIKOJA application in serving public needs and as an effort to realize bureaucratic reform within the Jambi City government. This study uses a qualitative method with a case study approach. This approach was chosen to gain a deep understanding of the application of Agile Governance principles in public services, particularly through the digital innovation of the SIKOJA (Jambi City Information System) application. The results of this study indicate that there are several principles that are considered unsuccessful in being implemented. As with the Human-focused principle, there are several important things that need to be improved, such as minimal socialization to users. The Systematic and Adaptive approach principle also explains that the Jambi City Government through the SIKOJA application has not been successful in implementing this principle. There are several complaints from users such as the system that often experiences errors and there are bugs or technical damage in the application.